Determinants of students’ academic success in English as a medium of instruction (EMI) classes: A systematic review - Lei Feng; Li He; Ayinuer Yiganmu (Heliyon, 2023)
With the rapid development of English as a medium of instruction (EMI), many education researchers have attempted to examine the extent to which EMI courses contribute to students' academic success. In a similar vein, several scholars have endeavored to locate the determinants of students' academic success in these courses. Given the fact that recognizing the predictors of academic success is of great help to educational administrators, teachers, and students, we aimed to uncover the various predictors of EMI students' academic success by scrutinizing the related research. In doing so, the relevant studies conducted on the antecedents of EMI students' academic success were identified through eight databases. Having gathered the related articles, we systematically reviewed the earlier investigations and their main findings. The review outcomes illuminated that English proficiency, vocabulary knowledge, academic self-concept, and self-efficacy are the important determinants of students’ academic success. Finally, the limitations of prior studies, the directions for future inquiries, and the practical implications of the current study are briefly discussed.